Practice of standard monitoring during anaesthesia in hospitals of North Kivu: a survey of health facilities of the health antenna of Butembo - Furaha Nzanzu Blaise Pascal; Paulin Kambale Musavuli; Joel Kambale Ketha; Franck Katembo Sikakulya; Andreas Barratt-Due; Thomas Castner; Gregor Pollach (BMC Health Services Research, 2020)
Abstract Background Standard monitoring during anaesthesia is a core element of patient safety and practice of safe anesthesia has reduced morbidity and mortality worldwide. The main objective of this study was to assess the practice of standard monitoring during anaesthesia in the hospitals of North Kivu, so as to establish a baseline overview of the situation, and orientate plans towards safe anaesthesia in the region. Methods This study was a cross-sectional survey of health facilities of the Health Antenna of Butembo in Democratic Republic of Congo and was conducted from October to December 2018. Questionnaires were brought to anaesthesia providers in the health facilities. The study included 1 answer from the anaesthesia practitioners who accepted to participate. The practices of standard monitoring in the health facilities were compared to WHO-WSFA guidelines. Data was captured and analyzed with Epi Info 7. Results Forty out of 90 health facilities (44.4%) of 10 health zones responded on the questionnaire. Twenty-three health facilities (57.5%) were from private sector and 17 (42.5%) from public sector. Sixteen health facilities (40.0%) were from the Butembo health zone. The median number of anaesthesia providers was 2 per health facility. Of all the anaesthesia providers, none were physicians, 47.5% were nurses practicing anaesthesia without any training in anaesthesia and 47.5% were nurse anaesthetists. All the health facilities were providing general anaesthesia whereas spinal anaesthesia was provided in 22 out of 40 centers (55%). Seventy percent (28/40) of the facilities were below standard according to WHO-WSFA guidelines. Only 40% (16/40) were using a pulse oximeter and 10% (4/40) declared that ECG was occasionally used. Conclusion The practice of standard monitoring is poor in health facilities of the Health Antenna of Butembo. Efforts should be made to improve monitoring which is a key element of safe anaesthesia.